Glucose-dependent insulinotropic polypeptide (GIP) and resistin as biomarkers in preeclampsia: Polipéptido insulinotrópico dependiente de glucosa (GIP) y resistina como biomarcadores en la preeclampsia - Israel, Anita; Camacho, Elsa; Matos, María Gabriela; Cortés, Rafael (Gaceta Médica de Caracas, 2025)
Introduction: The glucose-dependent insulinotropic polypeptide (GIP) is a hormone released in the small intestine in response to food intake. Its primary function is to regulate blood glucose homeostasis by stimulating insulin secretion. Preeclampsia (PE) is a syndrome exclusive to human pregnancy whose manifestations include high blood pressure, proteinuria, and edema. Its incidence increases in women with metabolic syndrome and insulin resistance. Pregnancy is a unique state characterized by physiological insulin resistance that resolves after delivery. The knowledge of the role of GIP in preeclampsia and gestational insulin resistance is scarce. Methods: Plasma levels of GIP, GLP-1, resistin and insulin were quantified in healthy pregnant women and those with PE, which belongs to a population of 30 Venezuelan women. Plasma samples were evaluated using multiplex bead analysis (Bio-Plex Pro Assays).